Peran Pendidikan Agama Islam Dalam Pembentukan Karakter Mulia Generasi Muda - Adinda Khoirunnisa Siregar; Tiffani Asnita Putri; Wianda Putri; Gusmaneli, Gusmaneli (CV. Ulil Albab Corp, 2023)
This journal explores the crucial role of Islamic religious education in forming character starting in the younger generation. Islamic religious education plays an important role in forming the noble character of the younger generation, through the teachings of morals, ethics and Islamic values, students are given a frame of mind to develop good and responsible behavior. Islamic religious education also provides guidance on piety, justice and empathy, which are essential for building a positive personality. By immersing themselves in Islamic religious values, the younger generation can become individuals who have integrity, independence and a sense of caring for others. Apart from that, Islamic religious education can help form an attitude of tolerance and respect for diversity, creating a harmonious and inclusive social environment. This research uses a literature analysis and empirical research approach, the author identifies the positive impact of Islamic religious learning on the development of morals, ethics and personality values in students. This article also highlights the challenges and opportunities in integrating Islamic religious teachings with character education in the context of modern education. The research results show that the effective implementation of Islamic religious education can make a significant contribution to the formation of noble character, providing a strong moral foundation for the younger generation to face the complex challenges of today's life.